2013
DOI: 10.1002/ejic.201201526
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Structure ofmer,trans‐[RuCl3(1H‐indazole)2(NO)], a Hypothetical Metabolite of the Antitumor Drug Candidate KP1019: An Experimental and DFT Study

Abstract: The study reported herein focused on the electronic structure of the {Ru(NO)} 6 fragment and characterization of the oxidation state of ruthenium in mer,trans- [RuCl 3 (Hind) (3) were experimentally and theoretically investigated as reference compounds. A complete active space SCF calculation was performed to estimate the extent of antiferromagnetic spin-spin coupling in 1. We found that the closed-shell structure {Ru III (NO) 0 } 6 fits better to the physical/ spectroscopic properties of 1, although {Ru … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 104 publications
(135 reference statements)
1
20
0
Order By: Relevance
“…In other words, when the equatorial H 2 O ligand is replaced by NO, the coordination of NO to Ru(III) produces the [Ru III (NO) 0 ] structure product. This outcome is in agreement with the result obtained by Bučinský and his coworkers . They showed that the closed‐shell structure [Ru III (NO)] 6 fits better with the physical/spectroscopic properties of mer,trans ‐[RuCl 3 (Hind) 2 (NO)].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, when the equatorial H 2 O ligand is replaced by NO, the coordination of NO to Ru(III) produces the [Ru III (NO) 0 ] structure product. This outcome is in agreement with the result obtained by Bučinský and his coworkers . They showed that the closed‐shell structure [Ru III (NO)] 6 fits better with the physical/spectroscopic properties of mer,trans ‐[RuCl 3 (Hind) 2 (NO)].…”
Section: Resultssupporting
confidence: 91%
“…Several ruthenium dimethyl sulfoxide nitrosyls have been synthesized and characterized by Alessio et al They indicated that the spectroscopic features are consistent with the [Ru(NO)] 6 formulation for all complexes because the ruthenium nitrosyls are formed by a diamagnetic Ru II nucleus bound to NO + . Experimental and DFT studies on the electronic structure of mer,trans ‐[RuCl 3 (1 H‐indazole) 2 (NO)] have been done by Bučinský and his coworkers . They showed that the physical/spectroscopic properties of mer,trans ‐[RuCl 3 (Hind) 2 (NO)] are better attributed to the closed‐shell structure [Ru III (NO)] 6 .…”
Section: Introductionmentioning
confidence: 99%
“…38 (H 2 ind) 2 [RuCl 5 (NO)] (Hind = 1 H -indazole) was prepared by heating the sodium salt with indazole in a 1:2 molar ratio in 6 M HCl. The starting compound ( n -Bu 4 N) 2 [OsCl 5 (NO)] was synthesized as previously reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…26 RuCl 3 and OsO 4 were purchased from Johnson Matthey. NH 2 OH·HCl, K 2 C 2 O 4 ·H 2 O, NaNO 2 , 1 H -indazole (Hind), 1 H -benzimidazole (Hbzim), 1 H -pyrazole (Hpz), and 1 H -imidazole (Him) were from Aldrich and Acros, while Na 15 NO 2 was from Cambridge Isotope Laboratories.…”
Section: Experimental Sectionmentioning
confidence: 99%